Some Lichens of North Eastern Langkawi and Gunung Machincang, Langkawi Islands - Zulkifly, Shahrizim; Feisal Merican, Amir (Malaysian Journal of Science, 2005)
A survey of lichen diversity and distribution was carried out during expeditions in Langkawi Islands in April 2003 and 2004. A total of 387 samples were collected from Gunung Machincang and the North Eastern Part of Langkawi comprising of Sungai Sireh, Datai, Gunung Raya, Ewa, KEDA housing area (Teluk Apau), Belanga Pecah, Lubuk Sembilang, Pulau Langgun, Sungai Kisap, Gua Cerita Area, Pulau Dendang and Teluk Mempelam. Morphological identification resulted in 36 genera of lichens, comprising of 32 micro lichens (crustose), and 4 macro lichens (foliose). The common microlichens obtained were from the Family of Graphidaceae and can be found from the sea level right up to the peak of Gunung Machincang. The most common foliose lichens found were Heterodermia sp. and Coccocarpia sp. This survey represents the first record of lichens in Langkawi Islands.